Fedratinib in patients with myelofibrosis previously treated with ruxolitinib: An updated analysis of the JAKARTA2 study using stringent criteria for ruxolitinib failure. Issue 6 (17th April 2020) - Harrison, Claire N.; Schaap, Nicolaas; Vannucchi, Alessandro M.; Kiladjian, Jean‐Jacques; Jourdan, Eric; Silver, Richard T.; Schouten, Harry C.; Passamonti, Francesco; Zweegman, Sonja; Talpaz, Moshe; Verstovsek, Srdan; Rose, Shelonitda; et al.
Abstract: Fedratinib is an oral, selective Janus kinase 2 (JAK2) inhibitor. The phase II JAKARTA2 study assessed fedratinib in patients with intermediate‐ or high‐risk myelofibrosis (MF) who were resistant or intolerant to prior ruxolitinib per investigator assessment. Patients received fedratinib 400 mg/day in 28‐day cycles. The JAKARTA2 outcomes were initially reported using a last‐observation‐carried forward (LOCF) analysis in a "Per Protocol" population. This updated analysis of JAKARTA2 employs intention‐to‐treat analysis principles without LOCF for all treated patients (ITT Population; N = 97), and for a patient subgroup who met more stringent definitions of prior ruxolitinib failure (Stringent Criteria Cohort; n = 79). Median duration of prior ruxolitinib exposure was 10.7 months. The primary endpoint was spleen volume response rate (SVRR; ≥35% spleen volume decrease from baseline to end of cycle 6 [EOC6]). The SVRR was 31% in the ITT Population and 30% in the Stringent Criteria Cohort. Median duration of spleen volume response was not reached. Symptom response rate (≥50% reduction from baseline to EOC6 in total symptom score [TSS] on the modified Myelofibrosis Symptom Assessment Form [MFSAF]) was 27%. Grade 3‐4 anemia and thrombocytopenia rates were 38% and 22%, respectively. Patients with advanced MF substantially pretreated with ruxolitinib attained robust spleen responses and reduced symptom burden with fedratinib.